Profile of an occupation – pharmaceutical technician - Schambeck, Arne [Verfasser] (My University, 2021)
"Pharmaceutical technicians control plants which produce tablets, ointments, powders and vaccines. The manufacture of vaccines is a complex and sensitive process which requires a particularly high degree of responsibility. This profile also presents trends which may expand the spectrum of tasks in future." (author's abstract; BIBB-Doku)
Berufe-Steckbrief: Pharmakant/Pharmakantin
Keywords: S 6.4.5.2 Übrige Gesundheitsberufe (außer Ärzte und Apotheker); 370; Laborberuf; Pharmakant; Pharmalaborant; Berufsbeschreibung; Tätigkeitsmerkmal